Grain Price Spikes and Beggar-Thy-Neighbor Policy Responses : A Global Economywide Analysis - Jensen, Hans G; Anderson, Kym (World Bank Group, Washington, DC, 2014)
When prices spike in international grain markets, national governments often reduce the extent to which that spike affects their domestic food markets. Those actions exacerbate the price spike and international welfare transfer associated with the terms of trade change. Several recent analyses have assessed the extent to which those policies contributed to the 2006-08 international price rise, but only by focusing on one commodity or using a back-of-the-envelope method. This paper provides a more comprehensive analysis that uses a global economywide model that is able to take account of the interactions between markets for farm products that are closely related in production or consumption. The model is able to estimate the impacts of those insulating policies on grain prices and on the grain trade and economic welfare of various countries. The results support the conclusion from earlier studies that there is a need for stronger World Trade Organization disciplines on export restrictions.